Arterioportal fistula causing jejunal variceal hemorrhage - Levent FİLİK and Bülent ÖDEMİŞ and Seyfettin KÖKLÜ and Muharrem TOLA and Mehmet YURDAKUL and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-